Struggle For Love In Chatherine Hardwicke's Twilight Movie: An Individual Psychological Approach - Aprita, Erwan Rahmat; , Drs. H. Abdillah Nugroho, M. Hum; , Titis Setyabudi, SS. M.Hum (2013)
The problem of this study is the struggle for love in several striving for superiority is reflected in Catherine Hardwicke's Twilight movie. The objective of this study is to analyze the movie based on the structural elements and to analyze the movie based on an individual psychological approach. The type of this research is a qualitative research. The object of this study is Object of the research in this case is Edward Cullen in Twilight movie. In introducing the research, the writer is going to analyze it by using individual psychological approach. There are two types of data source, first primary data source is Twilight movie directed by Catherine Hardwicke in 2008. While the second data source taken from books which have relation with the research and other materials that support this analysis. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the writer portrays some conclusions. First, based on structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, mise-en-Scene, cinematography, sound, casting and editing are supporting each other to produce a good quality movie. Second, based on the individual psychological analysis, the study shows there is a close relationship between Twilight movie and an individual psychology, particularly in human striving for superiority. There is a close relationship between Twilight movie and an individual psychology, particularly in human striving for superiority. Another key theme in the series is true love between mortal and immortal. With an exposition plot (like a usual movie) it makes the film easier to understand. This is a simple movie but with a great result.